Impact of COVID‐19 pandemic on emergency department patient volume and flow: Two countries, two hospitals. (25th September 2022) - Del Mar, Peter; Kim, Min Joung; Brown, Nathan J; Park, Joon Min; Chu, Kevin; Burke, John
Abstract: Objectives: COVID‐19 greatly disrupted the provision of emergency care across the globe. ED service delivery was urgently redesigned as human and material resources were mobilised, and patients with respiratory symptoms were isolated. This study aimed to compare ED patient volume and flow metrics before and during the COVID‐19 pandemic. Methods: An observational study was conducted in two large urban EDs in Brisbane, Australia and Seoul, Republic of Korea. Patient volume and flow were quantified using ED presentation numbers and service times, respectively. Daily case numbers, waiting, treatment and admission delay times were compared between 2019 and 2020/2021 using time series plots. Outcomes were further classified by triage category and age group. Trends were examined alongside a timeline of health service and government policies. Results: There were reductions in daily presentations for the least urgent triage categories during the early phase of the pandemic. The caseloads for the most urgent triage categories were unaffected. The trends were similar in both EDs. A reduction in waiting and admission delay times but not treatment times coincided with reduced presentations in Brisbane. This pattern gradually reversed as presentations returned to baseline. In Seoul, admission delay times returned to pre‐pandemic levels despite a persistent reduction in presentation numbers. Conclusions: Total daily presentations varied considerably according to government mandated social restrictions and testing requirements in both EDs. The reductions in waiting and admission delay times corresponded with improvements in hospital capacity. Abstract : The effect of the early COVID‐19 pandemic on ED patient volume and flow metrics were measured in two large urban EDs in Brisbane, Australia and Seoul, Republic of Korea. Total daily presentations varied considerably according to government mandated social restrictions and testing requirements in both EDs. The reductions in waiting and admission delay times corresponded with improvements in hospital capacity.